2014
DOI: 10.3109/21691401.2014.883401
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular system: Versatile carrier for transdermal delivery of bioactives

Abstract: The transdermal route of drug delivery has gained immense interest for pharmaceutical researchers. The major hurdle for diffusion of drugs and bioactives through transdermal route is the stratum corneum, the outermost layer of the skin. Currently, various approaches such as physical approach, chemical approach, and delivery carriers have been used to augment the transdermal delivery of bioactives. This review provides a brief overview of mechanism of drug transport across skin, different lipid vesicular system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 50 publications
0
55
0
3
Order By: Relevance
“…The release of the therapeutic agent occurs by the fusion of these vesicles into cell membranes in the deeper layers of the skin. 6,[124][125][126][127][128] It is suggested that transethosomes have superior skin-permeation properties over classical ethosomes. This is because transethosomes contain both ethanol and the edge activator or the penetration enhancer, which both act together to increase vesicular malleability and skin-lipid perturbation.…”
Section: Mechanisms Of Ethosomal System Skin Permeationmentioning
confidence: 99%
“…The release of the therapeutic agent occurs by the fusion of these vesicles into cell membranes in the deeper layers of the skin. 6,[124][125][126][127][128] It is suggested that transethosomes have superior skin-permeation properties over classical ethosomes. This is because transethosomes contain both ethanol and the edge activator or the penetration enhancer, which both act together to increase vesicular malleability and skin-lipid perturbation.…”
Section: Mechanisms Of Ethosomal System Skin Permeationmentioning
confidence: 99%
“…Benefits of local delivery are properly documented which includes targeted delivery, lower systemic exposure and lower toxicity than oral medications. This system is also helpfull in the treatment of hair loss, neuropathic pain, acne, genital herpes, migraine, headaches and sexual dysfunction (Singh et al, 2014a). It comprises list of advantages over conventional routes such as:…”
Section: Introductionmentioning
confidence: 99%
“…Recently, individual phytocompounds, such as curcumin, were developed using nanoniosome methods in the size range of 91 nm and showed enhanced skin protective activity. [208][209][210][211][212][213][214][215] From the earlier studies, phytocompound-containing nanoniosomes may be useful for both cosmeceuticals and pharmaceutical sectors.…”
Section: Nanoniosomesmentioning
confidence: 99%